Penerapan Model Pembelajaran Carousel Feedback Dalam Meningkatkan Hasil Belajar Siswa - Maryamah Maryamah; Fitri Oviyanti; Muhammad Wahyu Ilhami; Arivan Mahendra; Wiyanda Vera Nurfajriani (Cetta: Jurnal Ilmu Pendidikan, 2023)
The role of the teacher is crucial in determining the learning model and plays a vital role in student learning outcomes. The model chosen must be in accordance with the characteristics of the class, besides that students have a tendency not to listen to the teacher's explanation if students are less involved in the process, then the carousel feedback learning model can present the missing element, which is more involved students in the learning process. This research is an experimental research, and uses Pre-Experimental Designs research design with One-Group Pretest-Posttest Design research technique. The results of this study indicate that student learning outcomes before applying the carousel feedback learning model are known in the high category as many as 1 person or 3.9%, 21 people or 80.7% in the medium category, and 4 people or 15.4% in the low category, then student learning outcomes after applying the carousel feedback learning model in the high category as many as 3 people or 11.5%, 20 people or 77% in the medium category, and 3 people or 11.5% in the low category, so there is an increase in student learning outcomes before and after the application of the carousel feedback learning model. The increase in student learning outcomes in the high category from 3.9% to 11.5% is also reinforced by the results of hypothesis testing using IBM SPSS 26 which shows that the sig value. (2-tailed) is 0.00 0.05 which indicates that the hypothesis (Ha) is accepted and shows a significant difference, so it can be concluded that the application of carousel feedback learning media can improve the learning outcomes of ninth grade students in PAI subjects at SMP Negeri 55 Palembang.